3,5-Bis(arylidene)-4-piperidonesaspotential dengue proteaseinhibitors - Osman, Hasnah; Idris, Nor Hashima; Kamarulzaman, Ezatul Ezleen; A.Wahab, Habibah; Hassan, Mohd. Zaheen (Elsevier, 2017)
Dengue isaseveremosquito-borneviralinfectioncausinghalfamilliondeathsannually. Dengue virusNS2B/NS3proteaseisavalidatedtargetforanti-denguedrugdesign.Aseriesofhitherto unreported 3,5-bis(arylidene)-4-piperidonesanalogues 4a–4j were synthesizedandscreened in silico against DENV2NS2B/NS3proteasetoelucidatetheirbindingmechanismandorientationaroundthe active sites.Resultswerevalidatedthroughan in vitro DENV2 NS2B/NS3proteaseassayusinga fluorogenic Boc-Gly-Arg-Arg-AMCsubstrate.Nitroderivativesof3,5-bis(arylidene)-4-piperidones(4e and 4j) emergedaspromisingleadmoleculesfornovelproteaseinhibitorswithanIC50 of 15.22and 16.23 mmol/L, respectively,comparedtothestandard,panduratinA,havingIC50 of 57.28 mmol/L.